Complex of Fas-associated Factor 1 (FAF1) with Valosin-containing Protein (VCP)-Npl4-Ufd1 and Polyubiquitinated Proteins Promotes Endoplasmic Reticulum-associated Degradation (ERAD) - Lee, Jae-Jin; Park, Joon Kyu; Jeong, Jaeho; Jeon, Hyesung; Yoon, Jong-Bok; Kim, Eunice EunKyeong; Lee, Kong-Joo (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 2013)
Fas-associated factor 1 (FAF1) is a ubiquitin receptor containing multiple ubiquitin-related domains including ubiquitin-associated (UBA), ubiquitin-like (UBL) 1, UBL2, and ubiquitin regulatory X (UBX). We previously showed that N-terminal UBA domain recognizes Lys(48)-ubiquitin linkage to recruit polyubiquitinated proteins and that a C-terminal UBX domain interacts with valosin-containing protein (VCP). This study shows that FAF1 interacts only with VCP complexed with Npl4-Ufd1 heterodimer, a requirement for the recruitment of polyubiquitinated proteins to UBA domain. Intriguingly, VCP association to C-terminal UBX domain regulates ubiquitin binding to N-terminal UBA domain without direct interaction between UBA and UBX domains. These interactions are well characterized by structural and biochemical analysis. VCP-Npl4-Ufd1 complex is known as the machinery required for endoplasmic reticulum-associated degradation. We demonstrate here that FAF1 binds to VCP-Npl4-Ufd1 complex via UBX domain and polyubiquitinated proteins via UBA domain to promote endoplasmic reticulum-associated degradation.
Keywords: AAA ATPASE P97/VCP; POSTTRANSLATIONAL MODIFICATIONS; UBIQUITIN LIGASES; UBX DOMAIN; BINDING; IDENTIFICATION; CDC48/P97; COFACTORS; INTERACTS; STRATEGY